A comparison of kinesiophobia, pain-activity patterns and fear-avoidance beliefs in patients with chronic low back pain - Egemen Kızılay; Fatma Kızılay; Betül Ergün (Turkish Journal of Kinesiology)
Chronic pain affects individuals’ activity levels. Three activity patterns are observed among individuals with chronic pain: avoidance, overdoing, and regularization. According to fear - avoidance models, kinesiophobia is related to pain severity and disability. Kinesiophobia is a psychological factor that attracts attention in people with persistent pain, is related to the severity and persistence of pain. The aim of this study was to compare demographic and clinical characteristics of individuals with chronic inflammatory low back pain (ILBP) and mechanical low back pain (MLBP), in relation to kinesiophobia, fear-avoidance beliefs, and pain/activity patterns. A total of 89 people (45 MLBP, 44 ILBP) aged 18-65 were included in this cross-sectional study. A Visual Analog Scale (VAS) was used to inquire about for the duration of axial spondylarthritis diagnosis, duration of LBP, duration of morning stiffness, general pain, pain during movement, and night pain. Patients' fear of movement due to pain was assessed with the Tampa Kinesiophobia Scale (TKS), pattern changes in daily activities were assessed with the Pain-Activity Pattern Scale (PAPS), and fear-avoidance was assessed with the Fear-Avoidance Beliefs Questionnaire (FABQ). The scores obtained were compared. There was no statistically significant difference between the MLBP and ILBP groups in terms of age (p=0.202), BMI (p=0.124), gender (0.459), education level (p=0.082) and VAS-movement (p=0.071), FABQ score (0.277), PAPSa (p=0.454), PAPSe (0.596), PAPSs (p=0.247), and TKS score (p=0167). Whereas a statistically significant difference was found between the duration of morning stiffness (p=0.001), pain duration (p=0.018), VAS resting (p=0.001), and VAS night (p=0.001) score. It was observed that high resting and night VAS scores in the ILBP group were not associated with fear-avoidance and kinesiophobia behaviors any more than in the MLBP group. The fear- avoidance and kinesiophobia behaviors of both groups were affected to a similar extent, even though the pain type was different.